2016
DOI: 10.1210/en.2016-1247
|View full text |Cite
|
Sign up to set email alerts
|

The Angiotensin-(1–7)/Mas Axis Improves Pancreatic β-Cell Function in Vitro and in Vivo

Abstract: The angiotensin-converting enzyme 2/angiotensin (Ang)-(1-7)/Mas axis of the renin-angiotensin system often opposes the detrimental effects of the angiotensin-converting enzyme/Ang II/Ang II type 1 receptor axis and has been associated with beneficial effects on glucose homeostasis, whereas underlying mechanisms are mostly unknown. Here we investigate the effects of Ang-(1-7) and its receptor Mas on β-cell function. Isolated islets from Mas-deficient and wild-type mice were stimulated with Ang-(1-7) or its anta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 37 publications
1
35
0
Order By: Relevance
“…In fact, neprilysin hydrolyzes angiotensin I to angiotensin-(1–7) with greater efficiency than ACE2 (1). In comparing the expression pattern of neprilysin to ACE2 in islets, we (12) and others (21) have demonstrated that neprilysin is more widespread, because it is in both β-cells and non–β-cells. We show that ACE2 is limited to α, δ, and PP cells, which is in keeping with a recent report (22).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…In fact, neprilysin hydrolyzes angiotensin I to angiotensin-(1–7) with greater efficiency than ACE2 (1). In comparing the expression pattern of neprilysin to ACE2 in islets, we (12) and others (21) have demonstrated that neprilysin is more widespread, because it is in both β-cells and non–β-cells. We show that ACE2 is limited to α, δ, and PP cells, which is in keeping with a recent report (22).…”
Section: Discussionmentioning
confidence: 86%
“…Other histological reports do not clearly define the islet cell types expressing ACE2 (11,2325). One study (26) showed that ACE2 colocalized with both insulin and somatostatin, but rarely with glucagon and PP, whereas another study (21) showed ACE2 colocalized primarily with insulin. Inconsistency in descriptions of islet ACE2 localization could be due to species-specific differences in ACE2 expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…"Clearly, the development of the first antagonists with (subtype) selectivity for EPAC represents another research milestone to ascribe biologic responses to EPAC" (915). Indeed, these selective EPAC2 inhibitors are becoming effective tools in probing isoform-specific EPAC functions (18,47,130,175,226,250,302,411,463,565,682,743,841,896,961,1114).…”
Section: B Epac Specific Antagonistsmentioning
confidence: 99%
“…Ang(1–7) reverses hyperglycaemia and its consequences in an animal model of type 2 diabetes (Santos et al, ). Ang(1–7) regulates insulin secretion through a MAS‐dependent cAMP signalling pathway (Sahr et al, ).…”
Section: The Progress In Coupling Ang(1–7) Functions With Mas1 Receptorsmentioning
confidence: 99%